Personalização de projetos e obras em construtora de edificações residenciais : estudo de caso - Falconi, Taíssa Modesto Azevedo (2013)
Facing a highly competitive market the construction industry has adopted as one of the business strategies of offering customization of projects and works, seeking to focus on results that meet a demanding public and demand for differentiated products. The use of requirements for Quality Management Systems (QMS) based on the normative framework of the Quality and Productivity of the Habitat Agenda - PBQP- H specific to construction companies can support the process of customizing projects and the company works through the adoption procedure, inspections services and checklist. This case study was conducted in two stages. In the first step the bibliographic and documentary research, field observations, unstructured interview, diagnosis, which supported the current understanding of the business process customization was developed, which are the difficulties and interfaces generated between the agents involved. In the second stage of the work proposed guidelines and guides internal and external customization were established, as well as the process flow diagram for the proposed customization company.